Environmental protection and Authentic-Durable Happiness - Fei Fei; Liu Pingping (E3S Web of Conferences)
This study investigates the relationship between environmental protection behaviors and the development of authentic-durable happiness, aiming to promote a dual cycle of environmental protection and personal happiness. We collected 603 valid questionnaires and analyzed how environmental protection behaviors relate to basic psychological needs and well-being using self-determination theory. The results confirm that environmental protection behaviors are positively correlated with the satisfaction of basic psychological needs and subjective well-being. Moreover, these behaviors are significantly associated with authentic-durable happiness, highlighting the potential of environmental engagement as a pathway to sustained personal well-being and proactive environmental stewardship.